Possibilities of Application a Big Data in the Company Innovation Process - Koman, Gabriel; Kubina, Milan; Holubčík, Martin; Soviar, Jakub (Knowledge Management in Organizations, 2018)
Companies are inundated with huge amounts of data these days, whether from existing company’s systems or new information sources such as social media, mobile devices, fitness equipment etc. Many forward-thinking companies are finding that the Big Data can offer possibilities to support the innovation management process. New tools, methods and techniques for obtaining and processing various data can reveal new opportunities for realization of the economically successful innovation on the market.